(untitled) (Psychology Travelogs, 2024)
The article presents an analysis of psychological and pedagogical research on the problem of the influence of anxiety on self-esteem in young people. The content of the concepts: anxiety, anxiety, self-esteem of the individual is highlighted. It was determined that anxiety is a state, and anxiety is a personality trait, its peculiarity. Anxiety as a situational phenomenon characterizes the state of an individual at the moment, related to a specific external situation, and anxiety as a trait is a stable personality trait characterized by an increased tendency to experience anxiety due to real or imagined danger. It has been studied that anxiety arises in situations of uncertain danger, it is an emotional state that manifests itself due to the expectation of an unfavorable development of events. Self-esteem of a person is a person’s assessment of his qualities, himself, his abilities, as well as the place he occupies in the social environment. Self-esteem of an individual testifies to a person’s social adaptability, self-esteem is a regulator of behavior and activity that collects the entire life experience of a person. Varieties of anxiety are distinguished: situational and personal. As for personal anxiety, it is a personality trait and it manifests itself in the fact that a person constantly feels real or imagined danger. Personal anxiety is a basic trait that is formed, developed and consolidated in early childhood, and is an integrative negative individual property that determines an individual’s tendency to subjectively experience such emotional states as fear, excitement, tension. The factors of the manifestation of anxiety among student youth are identified: objective and subjective, which are manifested at such levels of the individual’s life activity as psychophysiological, social and psychological. Both self-esteem and anxiety are those characteristics that are very important for the formation and development of personality in youth, during educational activities, during formation in professional activities. It was found that anxiety has an influence on the formation and development of self-esteem of the youth.